1986
DOI: 10.1002/art.1780290301
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of treatment with naproxen in patients with rheumatic disease

Abstract: We evaluated the effects of a nonsteroidal antiinflammatory drug, naproxen, on phytohemagglutinin (PHA)–induced lymphocyte proliferation. When added in vitro to cultures of peripheral blood mononuclear cells, naproxen enhanced the proliferative response toward PHA of lymphocytes from rheumatoid arthritis (RA) patients but not from healthy volunteers, and it reduced prostaglandin E2 (PGE2) synthesis in the cultures. Oral treatment for 7 days with naproxen also resulted in a significant enhancement of the in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 30 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…In a recent study, RA patients and controls were reported to have increased PHA responsiveness following the administration of the NSAID naproxen (29). Similar findings have been previously described in RA patients treated with piroxicam (13).…”
Section: Discussionsupporting
confidence: 73%
“…In a recent study, RA patients and controls were reported to have increased PHA responsiveness following the administration of the NSAID naproxen (29). Similar findings have been previously described in RA patients treated with piroxicam (13).…”
Section: Discussionsupporting
confidence: 73%
“…It has become apparent that NSAIDs have considerable actions on the immune response and some of these actions may not be due to the inhibition of prostaglandin synthesis (Cueppens et al, 1986).…”
mentioning
confidence: 99%
“…A small number of studies have examined the pharmacokinetics of NSAIDs in 'responder' and 'non-responder' groups of subjects. It has become apparent that NSAIDs have considerable actions on the immune response and some of these actions may not be due to the inhibition of prostaglandin synthesis (Cueppens et al, 1986).…”
mentioning
confidence: 99%